Two new species and nomenclatural changes in the Cis castaneus species group (Coleoptera, Ciidae) - Królik, Roman (Zootaxa, 2016)
Cis hanseni A. Strand, 1965 is a junior synonym of Cis matchanus Reitter, 1915 stat. nov. The lectotype for Cis matchanus Reitter, 1915 is designated and illustrated, together with its original data labels. Two new species—Cis lasoni sp. nov. and Cis lugowoji sp. nov. from the Talysh and Alborz Mts. (Azerbaijan, Iran)—are described. The body and terminalia of males are illustrated in detail. The definition of the Cis castaneus species group is discussed.